The Crisis of the American Sense of Mission at the Turn of the Nineteenth and Twentieth Centuries - Szabó, Éva Eszter (Hungarian Journal of English and American Studies, 2022)
The sense of mission is an integral part of the national spirit. Therefore, questioning its validity can lead to the destabilization of a nation’s fundamental values and a major crisis in its self-image. This type of crisis accompanied the transformation of the American sense of mission at the turn of the nineteenth and twentieth centuries, which arose from the clash between the principles of traditional continental expansionism and new imperialist aspirations. In the wake of the 1898 Spanish-American War, the United States found itself definitively enmeshed in the global arena of great power politics. The control of overseas possessions not meant for statehood in the Union turned the federal republic into an empire in all but in its name. The crisis of the sense of mission fed on the inherent tension between liberal democratic traditions and the attempt made at imperial governance. As research into the Congressional Records will indicate, in the congressional debate developing between traditional and new ideas of expansionism, a consensus emerged that the questions relating to the status of the new overseas territories were the most significant the American people had faced during the nineteenth century, for these questions touched upon the roots of the nation’s consciousness. With view to the significance of this historical moment, this essay examines the forces at work both for and against the transformation of the American sense of mission at a time when Congress still constituted a powerful check on the executive in the field of foreign policy. (ÉESZ)